2014
DOI: 10.1002/ijc.29083
|View full text |Cite
|
Sign up to set email alerts
|

An Fc‐optimized NKG2D‐immunoglobulin G fusion protein for induction of natural killer cell reactivity against leukemia

Abstract: Recruitment of Fc-receptor-bearing effector cells, such as natural killer (NK) cells, is a feature critical for the therapeutic success of antitumor antibodies and can be improved by the modifications of an antibody's Fc part. The various ligands of the activating immunoreceptor NKG2D, NKG2DL) are selectively expressed on malignant cells including leukemia. We here took advantage of the tumor-associated expression of NKG2DL for targeting leukemic cells by NKG2D-immunoglobulin G (IgG)1 fusion proteins containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…NKG2D‐ligands mark cellular stress and they are expressed by many types of tumour cells that, as a consequence, can become targets for NKG2D. Indeed, the use of effector lymphocytes engineered to express NKG2D as therapy in cancer patients has already been translated into clinical trials and others have shown that Fc‐optimised NKG2D‐Fc constructs can induce NK cell antibody‐dependent cellular cytotoxicity against breast cancer and leukemic cells . However, although NKG2D can initiate cytotoxicity against a cell displaying NKG2D‐ligands at the surface, as we will discuss later, tumours can evade the immune response by releasing the ligand proteins.…”
Section: Nkg2d‐ligands: a Large Variety Of Cellular Stress Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…NKG2D‐ligands mark cellular stress and they are expressed by many types of tumour cells that, as a consequence, can become targets for NKG2D. Indeed, the use of effector lymphocytes engineered to express NKG2D as therapy in cancer patients has already been translated into clinical trials and others have shown that Fc‐optimised NKG2D‐Fc constructs can induce NK cell antibody‐dependent cellular cytotoxicity against breast cancer and leukemic cells . However, although NKG2D can initiate cytotoxicity against a cell displaying NKG2D‐ligands at the surface, as we will discuss later, tumours can evade the immune response by releasing the ligand proteins.…”
Section: Nkg2d‐ligands: a Large Variety Of Cellular Stress Indicatorsmentioning
confidence: 99%
“…Indeed, the use of effector lymphocytes engineered to express NKG2D as therapy in cancer patients has already been translated into clinical trials and others have shown that Fc-optimised NKG2D-Fc constructs can induce NK cell antibody-dependent cellular cytotoxicity against breast cancer and leukemic cells. 30,31 However, although NKG2D can initiate cytotoxicity against a cell displaying NKG2D-ligands at the surface, as we will discuss later, tumours can evade the immune response by releasing the ligand proteins. So, it is also important to study the dynamics and functional capacities of NKG2Dligands in order to understand properly this complex system as a whole, and to manipulate it for the benefit of patients.…”
Section: Nkg2d Receptormentioning
confidence: 99%
“…For instance, some of the novel or modified anti-CD20 mAb show an increased capability to trigger ADCC [9, 10, 15, 16, 20, 26, 39-46, 117, 118, 128, 160-162]. In addition, a NKG2D-Fc fusion protein was shown to trigger efficiently NK cell ADCC against NKG2D ligand-expressing tumor cells [168,169]. In addition, a NKG2D-Fc fusion protein was shown to trigger efficiently NK cell ADCC against NKG2D ligand-expressing tumor cells [168,169].…”
Section: Nk Cell-oriented Approaches To Enhance Therapeutic Efficacy mentioning
confidence: 99%
“…Along this line, bispecific and trispecific antibodies that bridge CD16 and tumor antigens represent a NK-oriented evolution of tumor-targeting mAb [3,42,[163][164][165][166][167]. In addition, a NKG2D-Fc fusion protein was shown to trigger efficiently NK cell ADCC against NKG2D ligand-expressing tumor cells [168,169]. Promising strategies that exploit the NKG2D activating receptor are represented by bispecific mAb directed against NKG2D/tumor antigen or by fusion proteins that link NKG2D ligands to an anti-tumor antigen mAb [95,96,135,170,171].…”
Section: Nk Cell-oriented Approaches To Enhance Therapeutic Efficacy mentioning
confidence: 99%
“…NKG2D can be involved in anti-tumor responses induced via IL-2 and IL-12 therapy, and also through CTLA-4 inhibitory receptor blockade [4547]. A NKG2D-Fc fusion protein was shown to efficiently trigger NK cell ADCC against NKG2D ligand-expressing tumor cells [48, 49]. Novel strategies that exploit the NKG2D activating receptor are represented by bispecific mAbs directed against an NKG2D-tumor-associated antigen or by fusion proteins that link NKG2D ligands to an anti-tumor antigen Fv region to bring NKG2D+ effector cells to tumor cells [5052].…”
Section: Nkg2d and Nk2gd Ligandsmentioning
confidence: 99%